Analisis Pengaruh E-commerce Terhadap Perilaku Konsumtif Mahasiswa (Studi Kasus Pada Mahasiswa Program Studi Bisnis Digital Universitas Bumigora) - Prasetyo, Rahman; Komala, Rina; Febriana, Widia (Universitas Bumigora, 2023)
The development of technology and the ease of information at this time is very influential in all aspects of life, for example the use of social media is not only used as a means of obtaining information and as a means of self-performance but social media is widely used as a means of doing business which we usually call an online shop. with increasingly evolving technology, there are now many online buying and selling sites which collect many online shops into one site that makes it easy for shoppers to get the items they want with various promos promising to attract students to shop there. In this study The researcher wants to know how the influence of the development of E-Commerce on the consumptive behavior of management students at Tidar State University. The method used in this study is descriptive qualitative method with a sample of 50 students majoring in Digital Business of the Bumigora University by distributing questionnaires. The results show that of the 26 samples taken it appears that the biggest effect of student consumptive behavior on E-commerce is caused by the promo or discount factor given by E-commerce sites at the beginning of the month.